Profil Sheikh Sulaiman Ar-Rasuli (1871 M – 1970 M) sebagai Pendakwah - Sarwan Sarwan (Universitas Islam Negeri Imam Bonjol Padang, 2012)
Sheikh Sulaiman Ar-Rasuli is a proselytizer who is from proselytizers generation. He has got Islamic education well either national or international. He is the old proselytizer that persevering defense ahlussunnah wal jamaah and mazhab Syafi’i faith. He gives Islamic preaching orally, written, and actions